Electromagnetic transient analysing of neutral bus in UHVDC converter station. Issue 16 (18th January 2019) - Wang, Yunchao; Yu, Zhanqing; Mou, Ya; Liu, Fan; Xie, Shijun; Shuiming, Chen; Zeng, Rong; He, Jingliang
Abstract : Transient processes at neutral bus of ultra‐high value direct current (UHVDC) converter station received insufficient attention, because of the lower amplitude compare to poles. However due to the lower insulation level, electromagnetic transient processes at neutral bus may cause serious fault, and become an important issue that should be studied carefully in the design stage. A method to analyse the electromagnetic transient based on time‐domain wide‐band circuit simulation is proposed in this study. Models of major equipment are described. The electromagnetic transient of a ±800 kV converter station is calculated. The transient under different operation statuses is compared. Effects of suppression method such as arresters and capacitors are analysed.